Financial and Institutional Quality: A Study on the Tourism Sector in Top Global Destinations - Felix Fisabilillah Bayu; Linda Rosalina; Wisnu Wibowo (LPPM Universitas PGRI Sumatera Barat, 2023)
This study analyzes the driving factors of the tourism sector in the top 17 global destinations based on International Tourism Highlights from 2000 to 2023. Using the GMM (Generalized Method of Moments) panel data method, this study specifically examines the role of financial development and institutional quality in developing the tourism sector. Our findings indicate that financial development has a positive and significant impact on the tourism sector in the short and long term. These results underscore that an efficient financial system and broad access to capital are important foundations for investment in the tourism sector. Conversely, the impact of institutional quality was positive but not consistently significant, implying that its role may be more facilitative or take longer to manifest. This study concludes that strengthening the financial system should be a key policy priority for governments promoting sustainable tourism. These findings make an important contribution to the tourism literature by providing comprehensive empirical evidence on the importance of these structural factors in shaping the global tourism landscape.